Recent Advances in the Pursuit of an Effective Acinetobacter baumannii Vaccine - Patrick S. Gellings; Ashley A. Wilkins; Lisa A. Morici (Pathogens, 2020)
Acinetobacter baumannii has been a major cause of nosocomial infections for decades. The absence of an available vaccine coupled with emerging multidrug resistance has prevented the medical community from effectively controlling this human pathogen. Furthermore, the ongoing pandemic caused by SARS-CoV-2 has increased the risk of hospitalized patients developing ventilator-associated pneumonia caused by bacterial opportunists including A. baumannii. The shortage of antibiotics in the development pipeline prompted the World Health Organization to designate A. baumannii a top priority for the development of new medical countermeasures, such as a vaccine. There are a number of important considerations associated with the development of an A. baumannii vaccine, including strain characteristics, diverse disease manifestations, and target population. In the past decade, research efforts have revealed a number of promising new immunization strategies that could culminate in a safe and protective vaccine against A. baumannii. In this review, we highlight the recent progress in the development of A. baumannii vaccines, discuss potential challenges, and propose future directions to achieve an effective intervention against this human pathogen.